Sexual Dimorphism of miRNAs Secreted by Bovine In vitro-produced Embryos - Gross, Nicole; Kropp, Jenna; Khatib, Hasan (Frontiers in Genetics, 2017)
Sexual dimorphism of bovine blastocysts has previously been observed through differences in development, cell death, metabolism, telomere length, DNA methylation, and transcriptomics. However, dimorphism in the secretion of miRNAs to culture media has not yet been evaluated. The objectives of this study were to determine if sex-specific blastocyst miRNA secretion occurs and to further investigate the role these miRNAs may have in the interaction between a blastocyst and the maternal environment. In vitro embryo culture was performed and media from male and female blastocysts was collected into sex-specific pools. Profiling of 68 miRNAs revealed a total of eight miRNAs that were differentially expressed between female and male-conditioned media. Validation by qPCR confirmed higher expression of miR-22 (P < 0.05), miR-122 (P < 0.05), and miR-320a (P < 0.05) in female media for three additional biological replicates. To examine the potential roles of secreted miRNAs to the media in communication with the maternal environment, miR-22, miR-122, and miR-320a were each supplemented to four replicates of primary bovine endometrial epithelial cell culture. Uptake of miR-122 (P < 0.05) and miR-320a (P < 0.05) was detected, and a trend of uptake was detected for miR-22 (P > 0.05). Further, expression of the progesterone receptor transcript, a predicted target of all three miRNAs, was found to be upregulated in the cells following supplementation of miR-122 (P < 0.05) and miR-320a (P < 0.05), and a trend upregulation of the transcript was observed following miR-22 (P > 0.05) supplementation. This work demonstrates that male and female conceptuses are able to differentially secrete miRNAs at the blastocyst stage and that these miRNAs have the ability to induce a transcriptomic response when applied to maternal cells. This knowledge builds on the known dimorphic differences in conceptuses at the blastocyst stage and demonstrates a role for blastocyst-secreted miRNAs in cell-cell communication.